DIFFERENTIATED INSTRUCTION IN MIXED-ABILITY ESL CLASSES: A PEDAGOGICAL RESPONSE TO LEARNER DIVERSITY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Mixed-ability ESL classrooms present one of the most persistent challenges in language education due to differences in learners’ proficiency levels, cognitive abilities, learning styles, motivation, and attention capacities. Traditional uniform teaching approaches often fail to accommodate this diversity, resulting in learner disengagement and unequal learning outcomes. This article provides an in-depth examination of differentiated instruction as a pedagogical framework for addressing mixed-ability ESL classes. Drawing on established educational theory and classroom practice, the article explores key principles of differentiation, practical instructional models, challenges faced by teachers, and pedagogical implications for inclusive language education. The findings suggest that differentiated instruction enhances learner participation, supports inclusivity, and promotes sustainable language development when systematically applied.